2016
DOI: 10.1002/jcb.25665
|View full text |Cite
|
Sign up to set email alerts
|

Intact NYN/PIN-Like Domain is Crucial for the Degradation of Inflammation-Related Transcripts by ZC3H12D

Abstract: ZC3H12D belongs to a recently discovered family of proteins containing four members of which the most studied and best described is the RNase ZC3H12A (MCPIP1/Regnase-1). ZC3H12A is a crucial negative regulator of inflammation. It accelerates the turnover of transcripts of a spectrum of proinflammatory cytokines, as well as its own mRNA. The biological role of ZC3H12D is less clear, although it was shown that this member of ZC3H12 family is also involved in the regulation of inflammation. Here, we show that ZC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 27 publications
1
39
0
Order By: Relevance
“…When comparing combined TMZ + OKN treatment to TMZ alone ( Figure 5 B ), interesting downregulated genes are IGR1 (associated with shorter disease-free survival in patients whose tumors are ER positive and HER2 positive [56] ; IGF1R signaling pathway is very relevant in drug resistance [57] ), XIST (increased level associated with shorter survival and poorer prognosis [58] ), and PRKDC (prognostic biomarker for chemoresistance in breast cancer patients [59] ). Interesting upregulated genes include ZC3H12A (crucial negative regulator of inflammation [60] ) and RN7SK (potential antiproliferative and tumor-suppressive function [61] ).…”
Section: Discussionmentioning
confidence: 99%
“…When comparing combined TMZ + OKN treatment to TMZ alone ( Figure 5 B ), interesting downregulated genes are IGR1 (associated with shorter disease-free survival in patients whose tumors are ER positive and HER2 positive [56] ; IGF1R signaling pathway is very relevant in drug resistance [57] ), XIST (increased level associated with shorter survival and poorer prognosis [58] ), and PRKDC (prognostic biomarker for chemoresistance in breast cancer patients [59] ). Interesting upregulated genes include ZC3H12A (crucial negative regulator of inflammation [60] ) and RN7SK (potential antiproliferative and tumor-suppressive function [61] ).…”
Section: Discussionmentioning
confidence: 99%
“…Interesting is also the phenomenon of the regulation of Regnase-1 level by other members of the ZC3H12 family. All proteins from this family (including Regnase-1 itself) are able to degrade Regnase-1 transcript (Iwasaki et al 2011;Wawro et al 2016Wawro et al , 2017M Wawro, A Solecka, W Sowinska, et al, unpubl.). In the present study, we have shown that ZC3H12B interacts with Regnase-1 3 ′ UTR although we could not confirm its direct interaction with Regnase-1 mRNA using RIP.…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, the V5-TC tag was excised with KpnI and NotI and the STreptagII-Flag tag was inserted by ligation of two phosphorylated and reannealed oligos (StrepFlagM2s: CCACCATGGCAAGCTGGAGCCACCCGCAGT TCGAAAAGGGTGCAGACTACAAAGACGATGACGACAAGCTT GC; StrepFlagM2s: GGCCGCAAGCTTGTCGTCATCGTCTTTG TAGTCTGCACCCTTTTCGAACTGCGGGTGGCTCCAGCTTGCC AT GGTGGGTAC spSBtet-GP was a gift from Eric Kowarz (Addgene plasmid #60495) (Kowarz et al 2015). The luciferase constructs (pmirGLO_IL-6-3 ′ UTR, pmirGLO_IL-6-3 ′ UTRΔCE, pmirGLO_ZC3H12A-3 ′ UTR, pmirGLO_VEGFA-3 ′ UTR, and pmir-GLO_IER3-3 ′ UTR) were described previously (Kochan et al 2016;Wawro et al 2016Wawro et al , 2017. The sequences of all used constructs were verified by Sanger sequencing (Genomed) and the expression of the recombinant proteins was confirmed by western blotting analysis.…”
Section: Plasmid Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zc3h12d is upregulated upon endotoxin exposure, and its knockdown leads to a strong increase in the levels of IL‐1β, IL‐6, and TNF‐α, as well as other transcripts encoding additional inflammatory factors . Degradation of these mRNAs depends on the intact RNase domain of Zc3h12d . Although Zc3h12a and Zc3h12d appear to target common transcripts and seem to interact by co‐immunoprecipitation, they act independently in degrading IL‐6 mRNA .…”
Section: Biological Roles Of Regnase‐1‐related Proteinsmentioning
confidence: 99%